To Hemoadsorb or Not to Hemoadsorb—Do We Have the Answer Yet? An Updated Meta-Analysis on the Use of CytoSorb in Sepsis and Septic Shock - Carmen Orban; Angelica Bratu; Mihaela Agapie; Tudor Borjog; Mugurel Jafal; Romina-Marina Sima; Oana Clementina Dumitrașcu; Mihai Popescu (Biomedicines)
Severe inflammation leading to organ dysfunction is the cornerstone of the pathophysiology of sepsis. Thus, from a theoretical point of view, rebalancing inflammation has the potential to improve patient outcomes. Methods: To better understand the clinical effectiveness of hemoadsorption in managing inflammation, we conducted an updated meta-analysis on the effects of CytoSorb in critically ill septic patients. Ten studies containing 715 patients (355 in the interventional group and 360 in the control group) have been included in the final analysis. Results: Statistical analysis demonstrated that the use of CytoSorb did not influence overall mortality (OR 0.95, 95% CI [0.58, 1.56], p = 0.85), but we observed a decreased mortality when comparing CytoSorb-treated patients with patients in the control group treated with continuous renal replacement therapy (CRRT) (OR 0.97, 95% CI [0.46, 0.98], p = 0.04). We also observed an increased mortality in patients in whom hemoadsorption was initiated earlier in the treatment course (OR 0.97, 95% CI [0.46, 0.98], p = 0.04). We did not observe any significant difference in either intensive care unit length of stay (p = 0.93) or between end-of-treatment severity scores in the two groups (p = 0.24). Conclusions: Although it has a high risk of bias, current evidence does not support the routine use of CytoSorb in critically ill septic patients. The addition of CytoSorb to CRRT may be associated with decreased survival as compared to CRRT alone, but future studies are needed to draw a definitive conclusion.